The Effect of Paclobutrazol Application Time and Variety on Growth, Yield, and Quality of Potato (Solanum tuberosum L.) - Ottilia Mabvongwe; Brenda T. Manenji; Munyaradzi Gwazane; Misheck Chandiposha (Advances in Agriculture)
An experiment was set up to investigate the effect of time of paclobutrazol application and variety on growth, yield, and quality of potato in a greenhouse at 34°C (±3) and 21°C (±3) day and night temperatures, respectively, with 60% relative humidity. The experiment was set up as a 2 × 4 factorial design in a CRD with 3 replications. The first factor was potato variety and the levels were BP1 and Diamond. The second factor was paclobutrazol application time and the levels were 28 (Days After Planting) DAP, 35 DAP, and 42 DAP and no paclobutrazol applied (control). Early application of paclobutrazol reduced stem length, number of tubers per plant, and sugar content of potato; furthermore, it increased starch content and yield compared to late application and no paclobutrazol treatments. Early application of paclobutrazol at 28 DAP is recommended in high temperature zones as it increased the yield by 108% and quality of potato.